Синтез и изготовление сложнопрофильных зубчатых колес - Воронцов, Б. С.; Бочарова, И. А.; Чаплинский, Д. А. (НТУ "ХПИ", 2009)
Розроблено методику визначення геометрії зубців зношених зубчастих коліс. Синтезовано зубчасті передачі з покращеною формою зубців. Отримані твердотільні комп'ютерні моделі, керуючі програми для верстата із ЧПУ, які були згенеровані та були виготовлені зубчасті колеса.

Methods of worn gear wheels teeth geometry definition has been worked out. Teeth gears having improved teeth form have been synthesized. Solid computer models have been obtained, controlling programs for numerically controlled machine-tools have been generated and gear wheels have been produced.
Keywords: эксплуатация; износ; поверхность зубьев; программный комплекс "СИНТЕЗ"